Using Agile Software Development Methods to Develop an Android-Based Student Competency Assessment - Surawan, Ghea Chandra; Haryanto, Haryanto (FKIP Universitas Lampung, 2023)
Using Agile Software Development Methods to Develop an Android-Based Student Competency Assessment. Objective: This study aimed to develop an android-based competency assessment application system, reveal the functionalities, feasibility, performance, validity and reliability of the apps. Methods: This research was designed using a research and development (R&D) with Agile software method applied in the development stages (Beck, 1999). Sixty-seven students and two teachers were selected purposively and expressed willingness to participate in this study. Findings: Black box testing revealed that all features have run well from the role of admin, educator, and student. Conclusion: An android-based competency assessment application was successfully developed and ready to be used as an accurate and reliable electronic assessment instrument. Keywords: assessment, students’ competency, applications research and developmentDOI: http://dx.doi.org/10.23960/jpp.v13.i2.202347